Forensic Accounting and Ethical Governance in Subsidised Energy Distribution: Evidence from Indonesia - Fuad Yanuar Akhmad Rifai (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2026)
This study examines how forensic accounting mechanisms, when complemented by maqāṣid al-sharīʿah–based ethical principles, can strengthen accountability, transparency, and fairness in Indonesia’s subsidised LPG distribution system. Specifically, it explores governance challenges—including weak internal controls, information asymmetry, ethical dilemmas, and limited public accountability literacy—and develops an integrative accountability framework to support ethical public governance. This study adopts an interpretive qualitative approach using in-depth interviews, limited field observations, and document analysis. Participants include government regulators, distribution agents, and public auditors involved in subsidy supervision. Data were analysed through thematic coding guided by forensic accounting indicators and maqāṣid-informed ethical considerations, with credibility ensured through triangulation and reflexive analysis. The findings indicate that governance inefficiencies largely arise from inadequate alignment between forensic control mechanisms and ethical accountability practices. While forensic accounting enhances transparency through evidence-based oversight, maqāṣid al-sharīʿah contributes an ethical foundation for distributive justice and public trust. Based on these findings, the study proposes an integrative accountability framework that connects technical control with ethical reasoning in public sector governance. The study suggests that policymakers strengthen fraud mitigation and governance quality by reinforcing forensic oversight alongside ethics-oriented capacity building grounded in principles of justice (‘adl), moral responsibility (amānah), and public welfare (maṣlaḥah). This study offers an integrative perspective on forensic accounting and maqāṣid al-sharīʿah in public sector governance, contributing to the literature on ethical accountability and value-based governance in subsidy management contexts.